2004
DOI: 10.1063/1.1718219
|View full text |Cite
|
Sign up to set email alerts
|

Collision complexes in dissociative single electron transfer between Ne2+ and N2

Abstract: Experiments involving the coincident detection of the two monocationic products (Ne+ and N+) from the dissociative electron transfer reaction between Ne2+ and N2 at 7.8 eV collision energy allow the nascent velocity vectors of the ionic and neutral (N) products to be determined. Examination of the correlations between these vectors shows that one pathway to the products involves the dissociation of a transitory collision complex (N2Ne2+).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The lifetime of N 2 + * before it dissociates was determined to be B100 fs, comparable to estimates for N 2 + * generated in similar experiments. 85 There is a spread in the observed exoergicities due to minor contributions from the involvement of Ar 2+ ( 3 P), N 2 + (F 2 S g + ) and N 2 + (G 2 P u or H 2 P u ) and higher energy dissociation limits of N + + N.…”
Section: Dissociative Single Electron Transfermentioning
confidence: 97%
See 1 more Smart Citation
“…The lifetime of N 2 + * before it dissociates was determined to be B100 fs, comparable to estimates for N 2 + * generated in similar experiments. 85 There is a spread in the observed exoergicities due to minor contributions from the involvement of Ar 2+ ( 3 P), N 2 + (F 2 S g + ) and N 2 + (G 2 P u or H 2 P u ) and higher energy dissociation limits of N + + N.…”
Section: Dissociative Single Electron Transfermentioning
confidence: 97%
“…The pairs spectrum we record following collisions of Ar 2+ with N 2 shows a clear peak corresponding to the formation of Ar + + N + : a DSET reaction. The general mechanism for dicationic DSET reactions has been well investigated, 37,64,[85][86][87] and involves an initial LZ style single electron transfer, populating a product cation in a dissociative state (e.g. N 2 + *), followed by subsequent dissociation of that ion.…”
Section: Dissociative Single Electron Transfermentioning
confidence: 99%
“…28,46,58,59 However, other isolated cases of dicationic electron transfer involving significant complexation, as we see for this reaction, have also been previously reported. 60,61 Fig . 3b shows the internal frame scattering of O + and O, relative to the Ar + ion.…”
Section: Formation Of Ar + and O +mentioning
confidence: 99%
“…A similar case of DSET via a collision complex was observed following collisions between Ne 2+ and N 2 . 60 In the Ne 2+ /N 2 collision system the dissociative SET reaction proceeded along two competing routes, via a collision complex, [NeN 2 ] 2+ , and via a fast-sequential pathway. The two different pathways could be distinguished by distinct peaks in the product ions' angular distributions.…”
Section: Formation Of Ar + and O +mentioning
confidence: 99%
“…[9][10][11]13,14,[18][19][20][21][22] Scattering experiments, employing crossed-beam mass spectrometers, guided ion beams and coincidence techniques, have also been used to elucidate the detailed mechanisms of dicationic SET reactivity, usually revealing a direct pathway. [9,11,14,[21][22][23][24][25][26][27][28] More recently, similar experiments have been performed to help understand the dynamics of double electron transfer (DET) reactions in dication-neutral collisions. [9] In parallel with these studies of dicationic electron transfer, laboratory studies have also revealed that molecular dications can take part in bond-forming reactivity at low collision energies in the centre-of-mass frame.…”
Section: Introductionmentioning
confidence: 99%